An Investigation into Mean and Volatility Spill-over effects: the Experience in Emerging Europe - Hudson, Sam (2010)
With the returns to mainstream asset classes, such as equities, proving less fruitful than they have been in the past, investors are looking for alternative sources of returns. One such alternative, is emerging markets. Focussing on the European experience, this dissertation attempts to evaluate the position of emerging markets in a global context. This is done by analysing the mean and volatility spill-over effects from developed to emerging markets. The results from this empirical study suggest that there are minimal mean spill-over effects, although volatility spill-over effects are present. This analysis, in addition to a consideration of market correlations, leads to the conclusion that emerging European countries are currently a portfolio diversification opportunity. However, the dynamic behaviour of market integration suggests that these markets may not provide a diversification opportunity in the long term.